Successful desensitization with 5-fluorouracil in a patient who developed anaphylaxis after 5-fluorouracil infusion - Erdem Çakmak, Mehmet; Oztop, Nida; Yeğit, Osman Ozan (Alergologia Polska - Polish Journal of Allergology, 2024)
5-Fluorouracil (5-FU) is a chemotherapeutic agent widely used in the treatment of gastrointestinal tract, skin and breast cancers. Hypersensitivity reactions may occur due to the use of chemotherapeutic drugs. The underlying mechanisms of hypersensitivity reactions to chemotherapeutic drugs are not clear and depend on the drugs. Hypersensitivity reactions may develop with both immunological and non-immunological mechanisms. 5-FU infusion chemotherapy may cause early types of life-threatening hypersensitivity reactions. If 5-FU infusion chemotherapy must be administered after an allergic reaction, it should be administered with a desensitization protocol. Life-threatening hypersensitivity reactions to 5-FU are rare in the literature. The case is here presented of a patient with metastatic gastric cancer who developed anaphylaxis during systemic 5-FU administration and was successfully desensitized to 5-FU.